Library Service Strategy in Optimizing Reading Interest in Digital Reading Corner in The Community - Mulianti, Esa; Mujahid, Mujahid; Suyuthi, Nurmadhani Fitri (Journal La Sociale, 2023)
This study aims to understand and analyze the management strategies of the Library Service in optimizing reading interest at the Digital Reading Corner (POCADI) in the community of Penajam Paser Utara Regency. The research was conducted at the Library Service of Penajam Paser Utara Regency over a two-month period, employing data collection methods through interviews, observations, and documentation. Primary data were obtained from interviews with the community regarding reading interest and the use of POCADI, while secondary data were taken from literature and other relevant sources. Data analysis was carried out through the steps of data reduction, data presentation, and conclusion drawing. The results indicate that the management strategies of the Library Service include improving accessibility and content quality, collaborating with schools and local communities to raise public awareness, and ensuring efficient and sustainable management. This study also provides recommendations for comparative analysis with other digital literacy centers, the development of additional programs, and literacy promotion in the community to further enhance reading interest.